For-profit versus Nonprofit Private Higher Education - Levy, Daniel (International Higher Education, 2009)
Distinctions between the three sectors of education -- public, private non-profit, and for-profit -- are often difficult to draw. While certain legally-mandated financial standards divide them, domestic and foreign for-profit institutions may look and behave like private non-profit institutions. Further complicating the equation are cross-border partnerships between these sectors.